YOGA GEMBIRA BAGI LANSIA HIPERTENSI - Sinarsari, Ni Made (JURNAL YOGA DAN KESEHATAN, 2020)
Elderly is a natural process that occurs in every human being. There is a decrease in the network's ability to repair itself, maintain function so that it is unable to withstand infections and damage that occurs. The elderly have several problems, one of which is hypertension. Hypertension in the elderly 140/90 mmHg. Hypertension in the elderly is largely isolated systolic hypertension (HST). Hypertension occupies 87% of cases in people aged over 50 years. Efforts related to handling hypertension in the elderly include conventional, traditional approaches. One effort that can be done is to do balance exercises (yoga). Yoga is very important for the elderly in improving the quality of life. Regular exercise can improve physical health, mental health, social relationships, reduce the risk of abusers and maintain elderly bodily functions